2017
DOI: 10.1155/2017/5675086
|View full text |Cite
|
Sign up to set email alerts
|

Direction-Dependent Effects of Combined Static and ELF Magnetic Fields on Cell Proliferation and Superoxide Radical Production

Abstract: Proliferation of human umbilical vein endothelial cells was stimulated by a nearly vertical 60 or 120 μT static magnetic field (MF) in comparison to cells that were shielded against MFs. When the static field was combined with an extremely low frequency (ELF) MF (18 Hz, 30 μT), proliferation was suppressed by a horizontal but not by a vertical ELF field. As these results suggested that the effects of an ELF MF depend on its direction in relation to the static MF, independent experiments were carried out to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
0
18
0
2
Order By: Relevance
“…Thus, the mitochondria-specific probe MitoSOX Red was employed to detect the superoxide production and to assess the integrity of mitochondria [64,65]. Several recent studies reported that the ROS formation in mitochondria may lead to mitochondrial superoxide production [44,66,67]. In this study, menadione treatment increases mitochondrial superoxide production after exposure to the increasing trend ( Figure 6).…”
Section: Discussionmentioning
confidence: 63%
“…Thus, the mitochondria-specific probe MitoSOX Red was employed to detect the superoxide production and to assess the integrity of mitochondria [64,65]. Several recent studies reported that the ROS formation in mitochondria may lead to mitochondrial superoxide production [44,66,67]. In this study, menadione treatment increases mitochondrial superoxide production after exposure to the increasing trend ( Figure 6).…”
Section: Discussionmentioning
confidence: 63%
“…Although the directionality is a crucial feature for a vector field like EMF, not until recent years have the bioelectromagnetic researchers begun to investigate the influence of the EMF direction on the bioelectromagnetic effects [11][12][13] . Naarala et al have reported that the relative orientation between static and extremely low frequency magnetic fields has an effect on cell proliferation and superoxide production [11] . Tian et al have demonstrated that constant magnetic fields in different directions yield distinct effects on cell growth rates, depending on cell types [12] .…”
Section: Introductionmentioning
confidence: 99%
“…(11) and similarly add more diagonal elements to the reaction operator in Eq. (12). The creation operators between different spin systems still follow Eq.…”
Section: E Resonance Frequency Spectrummentioning
confidence: 99%
“…A change in the concentrations of reactive oxygen species, O 11,12,45 Spin dynamics of this specific radical pair when exposed to radiofrequency radiation was explored using Mol-Spin as illustrated in Fig. 4, where the FADH • radical was simulated using 5 hyperfine interactions, while the superoxide radical was assumed to be in its most abundant form with nonmagnetic isotopes for the atomic nuclei.…”
Section: Reaction Yield Detected Magnetic Resonance (Rydmr)mentioning
confidence: 99%
See 1 more Smart Citation